Stomach Contents In Relation To Shell Length, Width, and Weight in the Gastropod Trochus niloticus L - Eddy Soekendarsi; Slamet Santosa (Jurnal Moluska Indonesia, 2022)
The stomach content of 66 individuals of Trochus niloticus contained 42 potential food taxa. The composition   reflected that the snails had grazed on the surface of dead corals. Chrysophyta, Chlorophyta, Rhodophyta, Foraminifera, Cyanophyta, and settled pelagic organisms were mixed with a large quantity of detritus and sand.  The snails measured 2.3-11.9 cm in shell length, 2.6-12.3 cm in shell width, 0.93-84.82 g in soft body wet weight, and the weight of stomach contents was 0.03-10.09 g. The relationship between shell length and weight of stomach content was y=0.0373 exp(0.5003x), r=0.91; between shell width and weight of stomach content: y=0.0325 exp(0.4974x), r=0.92, and between soft body wet weight and weight of stomach content: s=:0.1793   + 0.0785x, r=0.97.